Penerapan Algoritma Fuzzy C-Means Pada Penentuan Lokasi Gudang Pendukung PT. XYZ - Brian Christian; Lukman Hakim (AITI, 2019)
In data mining a series of processes are applied to extract information from a data set. PT. XYZ which has a lot of sales data that can be processed. In the company PT. XYZ which is engaged in the retail sector which has tight competition and develops rapidly, customer satisfaction is one of the things that need to be considered. It takes more than product quality, but service to customers is also important to win competition in sales and one that can be considered in customer satisfaction is the availability of products that customers want. Use of Clustering Method to classify objects based on similarity in characteristics, especially one of fuzzy clustering, that is, fuzzy C-means can be used to determine the distance and presence of each point in a cluster. In this study, fuzzy C-means is applied in determining the supporting warehouse of PT. XYZ is based on the clustering location of PT. XYZ which is represented as the Cartesian coordinates and the centroid of each cluster refers to the location of the supporting warehouse along with the grouping of outlets with the supporting warehouse.Using 3 clusters in 100 iterations the difference in objective function is 3.3e-8%, while the experiment using 4 clusters requires 39 iterations with an objective function difference of 1.1e-12%,then themore number of clusters will minimize the difference in objective functions for results with smaller errors.